POTRET PEREMPUAN AMERIKA AWAL ABAD 20 PADA DRAMA KARYA TENNESSEE WILLIAMS - riyatno riyatno (Jurnal Lingua Idea, 2016)
This research is an attempt to reveal the portrait of early twentieth century American women in Southern America in Williams’ plays The Glass Menagerie and A Streetcar Named Desire. There are three objectives of the research, namely the efforts of American women to survive after they cannot depend on others any longer, their basic reasons to do their efforts, and how they do the efforts in order to continue their lives. Using the literary sociology, the three objectives of the research are discussed in the two plays as the main sources and the criticisms and the social condition in America in the early twentieth century as the secondary sources. The result of the research shows that the early twentieth century American women in Southern America make some efforts in order to survive after the decline of Old South tradition. There are a lot of changes, including social and cultural values. They, however, cannot adapt themselves in the society and they still keep their old values. Consequently, they are not successful. By looking for men to become their husbands, they try to survive. They actually want to save their lives physically and economically, even though they want to keep their values.